Dilema Aliansi Keamanan Korea Selatan-Amerika Serikat: Studi kasus penempatan THAAD di Korea Selatan - Nadya Elvira (Frequency of International Relations (FETRIAN), 2022)
The research conducted as following below purposed to provide the explaination behind South Korea's rational decision in conducting the Three No's Policy agreement with Tiongkok as an effort to achieve normalization of relations between the two countries after the boycott of the entry of South Korean products into China because of China's rejection of the cooperation of the Terminal High Altitude Area Defense (THAAD) between South Korea and the United States. This research is analyzed using a conceptual framework called Rational Actor Model. Based on Graham T. Allison, Rational Actor Model is divided into four main indicators that is being considered during taking a decision, which are Goals and Objectives, Alternatives, Consequences, and Choice. This research analyze South Korea's rational reasons for approving the policy through a literature study using the four elements described by Allison above. According to the Rational Actor Model itself, this research found that the economic factor is the main reason why South Korea finally decided to take the Three No's Policy agreement moreover considering the entire boycott towards South Korea's products that is being done by Tiongkok beforehand. This research found that South Korea's reason for agreeing to Three No’s Policy regarding the issue of a boycott by China against South Korea was due to economic factors. Although also confronted with alternatives regarding security policies, maintaining relations with China is more rational for South Korea because of the large economic interests of South Korea towards China. That is because China is the main trading partner and the biggest market for South Korea.